Left Ventricular Outflow Tract Area Measurements by Planimetry Using Two-Dimensional Simultaneous Orthogonal Plane Imaging During Transesophageal Echocardiography - Dwarakanath, Sanjay; Sharma, Gyanendra; Arthur, Mary E. (Journal of cardiothoracic and vascular anesthesia, 2016)
Calculations of the left ventricular outflow tract (LVOT) area are typically based on the assumption that the LVOT is circular. This study was conducted to determine whether simultaneous orthogonal plane imaging with tilt during two-dimensional (2D) transesophageal echocardiography provided more accurate measurements of the LVOT area than the standard method. The authors prospectively measured the LVOT area in 2D by (1) the standard calculation based on the diameter as viewed on the long axis, and (2) a direct measurement using planimetry of the short axis, in consecutive patients presenting for elective surgery. The authors validated the planimetric technique by obtaining three-dimensional (3D) measurements in a subset of the subjects. An academic medical center. Adult surgical patients with no evidence of aortic stenosis. Transesophageal images were acquired by anesthesiologists certified by the National Board of Echocardiography. Image acquisition and assessment were performed in the operating room and found to be adequate for analysis in 52 of 55 subjects. Simultaneous orthogonal plane imaging with tilt enabled long- and short-axis visualization of the LVOT. The authors found that the standard method underestimated the area by 0.78 cm2 compared to the direct method (2D planimetry) when measured at the same beat at a similar point in the cardiac cycle. Moreover, 2D planimetry measurements were comparable to 3D planimetry measurements in the last 20 study subjects (R2 = 0.88, p<0.0001). This study suggested that 2D planimetry may be more accurate than 2D diameter-based calculations.